Pengaruh Usaha Kecil Menengah (UKM) Opak Gambir terhadap Kesejahteraan Masyarakat Dusun Sentul Desa Winongan Kabupaten Pasuruan - Indarti, Nunuk; Pradikto, Sugeng; Sobakh, Nurus (Business and Accounting Education Journal, 2023)
This study aims to find out: 1). Small and Medium Enterprises opak gambir; 2). Community Welfare of Sentul Hamlet, Winongan Village; 3). The Influence of Opak Gambir Small and Medium Enterprises on the Welfare of the People of Sentul Hamlet, Winongan Lor Village.This study used a quantitative descriptive design using simple regression. Data were obtained using a closed questionnaire Likert scale and five alternative answers. The subject in this study was the owner of opak gambir UKM in Sentul Hamlet, Winongan Lor Village, Winongan District.